2012
DOI: 10.1108/13620431211280123
|View full text |Cite
|
Sign up to set email alerts
|

Don't leave your heart at home

Abstract: Purpose-The main objective of this study is to apply broaden-and-build theory to occupational wellbeing. More specifically, it seeks to test whether positive emotions "build" resources and to what extent they contribute to work engagement through an increase in personal or job resources. Additionally, it aims to hypothesize that positive emotions, resources, and work engagement are reciprocally related to each other in a way akin to a gain cycle. Design/methodology/approach-In order to test whether positive em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 65 publications
(88 reference statements)
2
24
0
3
Order By: Relevance
“…The group of attributes that received most attention was self-efficacy, resilience and personal resources; in other words, the positive perceptions that individuals hold of their personal strength and belief in their own ability, which featured in 10 studies. 111,119,141,215,228,229,265,[276][277][278] These studies show a positive association between these factors and engagement. For instance, Ouweneel et al 265 surveyed individuals at two time points and found that personal resources at time 1 were associated with engagement at time 2.…”
Section: Individual Psychological Statesmentioning
confidence: 83%
See 3 more Smart Citations
“…The group of attributes that received most attention was self-efficacy, resilience and personal resources; in other words, the positive perceptions that individuals hold of their personal strength and belief in their own ability, which featured in 10 studies. 111,119,141,215,228,229,265,[276][277][278] These studies show a positive association between these factors and engagement. For instance, Ouweneel et al 265 surveyed individuals at two time points and found that personal resources at time 1 were associated with engagement at time 2.…”
Section: Individual Psychological Statesmentioning
confidence: 83%
“…111,119,141,215,228,229,265,[276][277][278] These studies show a positive association between these factors and engagement. For instance, Ouweneel et al 265 surveyed individuals at two time points and found that personal resources at time 1 were associated with engagement at time 2. A large number of these studies used complex methods such as diary studies, time-lagged surveys or supervisor/ employee dyads, which lends additional weight to the findings.…”
Section: Individual Psychological Statesmentioning
confidence: 83%
See 2 more Smart Citations
“…Individuals who possess high levels of hope display high levels of positive expectancy and their energy is fuelled toward the attainment of that goal. Such drive to attain a particular goal results in higher levels of engagement (Ouweneel et al 2012). Several researchers subdivided hope into two components: willpower and pathways (Snyder 2000;Snyder, Feldman, & Taylor 2000;Snyder & Lopez 2002).…”
Section: Hopementioning
confidence: 99%